Dual trigger for final oocyte maturation in expected normal responders with a high immature oocyte rate: a randomized controlled trial - Yan, Meng-Han; Sun, Zhen-Gao; Song, Jing-Yan (Frontiers in Medicine, 2023)
Objective To evaluate whether dual trigger could improve reproductive outcomes in women with low oocyte maturation rates compare to human chorionic gonadotropin (hCG) trigger. Methods This study included expected normal ovarian responders younger than 40 years old whose immature oocyte rate in the previous cycle was more than 50% at the reproductive center from July 2021 to November 2022. A total of 73 patients were enrolled at trigger, including 34 in the hCG trigger group and 39 in the dual trigger group (co-administration of gonadotrophin releasing hormone (GnRH) agonist and hCG, 40 and 34 h prior to oocyte retrieval, respectively). The primary outcome was oocyte maturation rate. Results There was no significant difference in the number of oocytes retrieved between the two study groups, but the oocyte maturation rate was higher in dual trigger group (84.0% [14.0%] vs. 55.5% [19.8%], p < 0.001). Moreover, there were also higher cumulative pregnancy rate (69.4% vs. 40.0%, p = 0.035) and cumulative live birth rate (66.7% vs. 36.0%, p = 0.022) in dual trigger group. Conclusion For normal responders with low oocyte maturation rates, the dual trigger may be more effective than the conventional hCG trigger. Clinical trial registration ClinicalTrials.gov, identifier ChiCTR2100049292.